Estrategias de marketing y su influencia en el posicionamiento de la Universidad Privada de Trujillo 2018 - Vargas Bravo, Susana (2019)
The present investigation has like objective the study, the strategies of marketing and its influence in the positioning of the Private University of Trujillo in the year 2018. This is a non-experimental study and the design of the research is transversal descriptive; for the counting of data it is used as a questionnaire instrument, with a significance level of Cronbach's Alpha with oscillating values between 0.637, which validates the survey. The sample was represented by 266 students from the different private schools of Trujillo, the results were processed in the Excel spreadsheet and the statistical program SPSS to process and process research data, to determine the influence of marketing strategies and the positioning of the private university of Trujillo refers to Pearson's correlation coefficient. Obtaining as a result a negative Pearson correlation coefficient (r = -0.425), where we conclude that the marketing strategies are used for the company does not influence the positioning, that the Private University of Trujillo applies the marketing of the 4P'S. 5th place in the market. For all this is recommended in a general way Restructuring your marketing plan is based on the service, the price, the place, the promotion, which is not about the strategies properly, with special emphasis on promotion through the internet since it was demonstrated that it is the medium most used by our study population with 34%.